For a lesson on Ferdinando Bandini's "Berceuse" (Prassi Ecdotiche della Modernità Letteraria, 2017)
Fernando Bandini Archives (stored up at the Biblioteca dell’Accademia Olimpica in Vicenza) includes a folder (Envelope G/III, 39) that contains manuscripts, typographies, photocopies of prints and pages extracted from publications in magazines related to twenty-five poems of Santi di Dicembre (Milano, Garzanti, 1994). The study describes two typescripts of Berceuse and traces the poem correction process from the first steps up to the printed version in volume. A proposal for a critical edition ends the study.
Keywords: Ferdinando Bandini; Berceuse; archives; critical edition; correction process; poetry; collection